2004
DOI: 10.1002/ptr.1503
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the analgesic, anti‐inflammatory and anti‐diabetic properties of Sclerocarya birrea (A. Rich.) Hochst. stem‐bark aqueous extract in mice and rats

Abstract: In order to appraise some of the ethnomedical uses of Sclerocarya birrea (A. Rich.) Hochst., subspecies caffra (Sond.) Kokwaro [family: Anacardiaceae], the present study was undertaken to investigate the analgesic, anti-inflammatory and anti-diabetic properties of the plant's stem-bark aqueous extract in experimental models of pain, inflammation and diabetes mellitus. The analgesic effect of Sclerocarya birrea stem-bark aqueous extract was evaluated in mice, while its anti-inflammatory and anti-diabetic effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(53 citation statements)
references
References 32 publications
(38 reference statements)
3
43
0
2
Order By: Relevance
“…This is a direct way to diminish the release of arachidonic acid by neutrophils and other immune cells. [53] The used dose of diclofenac sodium in this work was reported [25,26,54] and the results showed that diclofenac sodium enhanced the activity of liver enzymes. This finding suggests increased transmembrane transport of diclofenac sodium and metabolized it in the liver to 4-hydroxy diclofenac and other hydroxylated forms after glucoronidation and sulfation before being eliminated principally via urinary and biliary excretions, [55] where liver enzymes, especially, alkaline phosphatase, are involved in the absorption and transportation across canalicular membrane proteins.…”
Section: Screening Of Anti-inflammatory Activity Of Vicine and Divicinementioning
confidence: 79%
See 1 more Smart Citation
“…This is a direct way to diminish the release of arachidonic acid by neutrophils and other immune cells. [53] The used dose of diclofenac sodium in this work was reported [25,26,54] and the results showed that diclofenac sodium enhanced the activity of liver enzymes. This finding suggests increased transmembrane transport of diclofenac sodium and metabolized it in the liver to 4-hydroxy diclofenac and other hydroxylated forms after glucoronidation and sulfation before being eliminated principally via urinary and biliary excretions, [55] where liver enzymes, especially, alkaline phosphatase, are involved in the absorption and transportation across canalicular membrane proteins.…”
Section: Screening Of Anti-inflammatory Activity Of Vicine and Divicinementioning
confidence: 79%
“…(100 mg/kg orally suspended in distilled water). [25,26] The rat hind paw oedema was used as a model of acute inflammation. Rat hind paw oedema was induced by intraplantar injection of fresh egg albumin (0.5 ml/kg).…”
Section: Evaluation Of Anti-inflammatory Propertymentioning
confidence: 99%
“…The change in volume due to carrageenin-induced paw swelling (Vt) of the paw was measured at 0, 30 min, 1, 2, 3, 4, 5 and 6 h after, using plethysmographic method. The percent inhibition was calculated using the modified formula 7,8 below: …”
Section: Effects On Carrageenin-induced Paw Edemamentioning
confidence: 99%
“…Chasmanthera dependens (Morebise et al, 2001); Acanthus montanus (Adeyemi et al, 2004); Bysorcarpus coccineus (Akindele and Adeyemi, 2007), Stereospermum kunthianum (Ching et al, 2009), Sclerocarya birrea (Ojewole, 2004), Harpagophytum procumbens (Mahomed and Oyewole, 2004;Anilkumar, 2010), Tithonia diversifolia (Owoyele et al, 2004), Palisota hirsuta ( Wood et al, 2009;Boakye-Gyasi et al, 2011), Zingiber officinale (Ojewole, 2006;Anilkumar, 2010), Hippocratea indica and Poga oleosa (Ogbole et al, 2007), Securidaca longepedunculata (Ojewole, 2008), Tetrapleura tetraptera (Ojewole, 2009), Parquetina nigrescens (Owoyele et al, 2008), Hunteria umbellate (Adeneye et al, 2011).…”
Section: Pharmacological Activity Of Some Plants Used In the Treatmenmentioning
confidence: 99%